1998
DOI: 10.1126/science.279.5357.1714
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Map Reorganization Enabled by Nucleus Basalis Activity

Abstract: Little is known about the mechanisms that allow the cortex to selectively improve the neural representations of behaviorally important stimuli while ignoring irrelevant stimuli. Diffuse neuromodulatory systems may facilitate cortical plasticity by acting as teachers to mark important stimuli. This study demonstrates that episodic electrical stimulation of the nucleus basalis, paired with an auditory stimulus, results in a massive progressive reorganization of the primary auditory cortex in the adult rat. Recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
808
3
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,120 publications
(849 citation statements)
references
References 35 publications
36
808
3
2
Order By: Relevance
“…Rats were repeatedly presented with a midfrequency pure tone over the course of 20 days either with or without paired VNS, followed by auditory mapping to derive the frequency map in primary auditory cortex. Consistent with previous studies, repeated presentation of tones without VNS did not induce map reorganization [33]. However, presentation of the same number of tones paired with VNS significantly increased the proportion of neurons that responded to frequencies near the paired tone.…”
Section: Enhancing Plasticity With Vns Vns Paired With Tones Drives Rsupporting
confidence: 90%
See 1 more Smart Citation
“…Rats were repeatedly presented with a midfrequency pure tone over the course of 20 days either with or without paired VNS, followed by auditory mapping to derive the frequency map in primary auditory cortex. Consistent with previous studies, repeated presentation of tones without VNS did not induce map reorganization [33]. However, presentation of the same number of tones paired with VNS significantly increased the proportion of neurons that responded to frequencies near the paired tone.…”
Section: Enhancing Plasticity With Vns Vns Paired With Tones Drives Rsupporting
confidence: 90%
“…VNS drives activity in the cholinergic basal forebrain, providing a potential pathway to enhance plasticity [15,33]. Our recent study directly tested whether the nucleus basalis (NB), a primary component of the cholinergic basal forebrain, is required for VNS-dependent enhancement of map plasticity in motor cortex.…”
Section: Vns Paired With Forelimb Training Enhances Reorganization Ofmentioning
confidence: 99%
“…Experimental results (Singer and Rauschecker, 1982;Kilgard and Merzenich, 1998) and modeling work (Hasselmo, 1993;Sánchez-Montañés et al, 2000) have shown that cholinergic modulation is an essential ingredient in cortical plasticity. The model predicts how strong ACh release, such as during repeated mismatches, or as a consequence of an environmental stressor, can influence the sharpness of the neural code, by altering the degree of match required for bottom-up and top-down matches to prevent reset.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed descriptions of experimental preparation and microelectrode mapping techniques can be found in previous publications (Kilgard and Merzenich, 1998a, 1998bKilgard et al, 2001a,b) and are described in brief below.…”
Section: Methodsmentioning
confidence: 99%